RETRACTED: Prognostic influence of PD-1/PD-L1 suppressors in combination with chemotherapeutic agents for non-small cell pulmonary carcinoma: system review and meta-analysis - Shen, Min; Lu, Chunxia; Gao, Jie (Frontiers in Oncology, 2023)
Background: Lung cancer is a common malignant tumor, which is seriously harmful to human life and health. Nowadays, it has gradually become one of the best treatments for non-small cell lung cancer (NSCLC) to combine immunotherapy and chemotherapy, and its clinical efficacy is preliminary. Nevertheless, substantial differences exist between various studies and various indicators. Despite their unconvincing results, high-quality research evidence is needed to support them. In this case, further correlative studies are necessary to investigate the prognostic outcomes of PD-1/PD-L1 suppressors in combination with chemotherapeutic drugs in NSCLC. Methods: The online public databases were searchable for the clinical trials that consisted of NSCLC patients who had concluded their chemotherapy and who had accepted PD-1/PD-L1 suppressors. The time-span of the search spanned from the beginning to the end of the database. Two investigators retrieved the data independently. RevMan 5.3 statistical software was utilized for the assessment of bias risk. The software followed the Cochrane Handbook 5.3 guidelines. Results: There were seven clinically controlled studies with 2781 samples finally included in this study. A meta-analysis of the post-treatment overall response rate (ORR) was undertaken. A remarkably higher ORR rate was observed in the study group (p<0.05). Study participants had a noticeably longer PFS (HR=0.61, 95% CI=0.54-0.70, P<0.00001). Study participants had markedly longer overall survival (OS) (HR=0.651, 95% CI=0.52-0.82, P<0.05). The incidence of adverse events (AEs) of Grade 3 or above was not clinically clearly different (P>0.05), as demonstrated by the incidence of AEs. The funnel plots were separately charted in accordance with ORR rate, PFE, OS, and Grade 3 AEs. Conclusion: The combined PD-1/PD-L1 inhibitors with conventional chemotherapy can dramatically elevate the prognosis of NSCLC patients, obviously enhancing the ORR rate and prolonging their PFS and OS. Furthermore, it was found that adding PD-1/PD-L1 inhibitors to conventional chemotherapy did not result in any additional adverse effects. Nevertheless, we suggest that this combination regimen needs more detailed examinations and longer follow-up for further verification.